Individual variability of salivary gland proteins in three Phlebotomus species - Rohoušová, Iva; Volfová, Věra; Nová, Soňa; Volf, Petr (Acta tropica, 2012)
Pooled salivary gland samples are frequently used to ensure the sufficient amount of material for the experiments; however, this could mask an individual variability. Thus, we compared salivary protein profiles in seven colonies of three Phlebotomus species: Phlebotomus sergenti, Phlebotomus perniciosus, and Phlebotomus papatasi. Surprisingly, the individual profiles differed significantly between the colonies as well as between individuals. The highest variability was observed in proteins with molecular masses of 42-46 kDa corresponding to the yellow-related proteins. The phenogram constructed from salivary gland profiles revealed the existence of two main groups in P. sergenti, corresponding well with the geographical origin. The F1 progeny obtained from cross-mating studies between P. sergenti colonies of different geographical origin formed a distinct subgroup within the parental groups. In P. papatasi, several groups of protein profiles were observed with no relationship to the geographical origin. The biological role of salivary proteins variability is discussed.
Keywords: Molecular Weight; elektroforéza v polyakrylamidovém gelu; křížení genetické; molekulová hmotnost; Crosses, Genetic; mužské pohlaví; Salivary Glands; fenotyp; Phlebotomus; Cluster Analysis; slinné proteiny a peptidy; Salivary Proteins and Peptides; Phenotype; Electrophoresis, Polyacrylamide Gel; ženské pohlaví; Proteome; zvířata; slinné žlázy; proteom; Female; shluková analýza; Male; Animals